Analysis of walkability and access to transit areas for transit node development in the Bangkok Metropolitan Region, Thailand - Issaree Jitrpatima; Kim, Sohee Minsun; Vilas Nitivattananon; Surachet Pravinvongvuth; Thailand (HM Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
In year 2016, BMR was considered as one of the worst traffic congestion city in the world. Therefore, Bangkok Mass Transit System was established for improving the quality of life for Bangkok's population by delivering safe and punctual mass transit solutions. To pursue the mentioned goal, this study aims to promote the maximize benefit of transit node development area by improving pedestrian walkability and effective way of area management in Bangkok. This study considers the influence factors of walking frequent walking distance and transit use in three main aspect which are area physical factors, walkway quality factors and pedestrian factors. The study areas are chosen from the mass transit node that have potential to be developed under TOD concept in Thailand which are Makkasan station and Bangsue station. Both qualitative and quantitative methods is applied by using primary and secondary data source. To pursue study objectives, data are analyzed in both quantitative and qualitative methods which are location analysis, network and accessibility analysis, connectivity analysis, Pedshed analysis and factor relations analysis. In addition, walkability solutions and recommendation are suggested according to walkability improvement scenarios linked to walkability and accessibility factor analysis. The results of the study can contributed to pedestrian network and pedestrian ftiendly environment improvement to elevate the level of mass transit accessibility and transit surrounding area development such as transit oriented development in the future.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental Management
Thesis (M. Sc.) - Asian Institute of Technology, 2018
Keywords: Thailand -- Bangkok -- Transit systems; Transit-oriented development -- Thailand -- Bangkok